Parental thermal conditions affect the brain activity response to alarm cue in larval zebrafish - Sourisse,Jade M.; Semmelhack,Julie L.; Schunter,Celia (PeerJ, 2024)
Temperature is a crucial factor affecting the physiology of ectothermic animals, but exposure to elevated temperature during specific life stages and across generations may confer fish resilience through phenotypic plasticity. In this study, we investigate the effects of developmental and parental temperature on brain activity response to an olfactory cue in the larval zebrafish, Danio rerio. We exposed parents during reproduction and their offspring during development to control (28 °C) or elevated temperature (30 °C) and observed the response of the larval telencephalon to an alarm cue using live calcium imaging. Parental exposure to elevated temperature decreased the time till maximum brain activity response regardless of the offspring’s developmental temperature, revealing that parental thermal conditions can affect the excitability of the offspring’s neural circuitry. Furthermore, brain activity duration was affected by the interaction between parental and offspring thermal conditions, where longer brain activity duration was seen when either parents or offspring were exposed to elevated temperature. Conversely, we found shorter brain activity duration when the offspring were exposed to the same temperature as their parents, in both control and elevated temperature. This could represent an anticipatory parental effect influencing the offspring’s brain response to match the parental environment, or an early developmental effect occurring within a susceptible short time window post-fertilization. Overall, our results suggest that warming can alter processes involved in brain transmission and show that parental conditions could aid in the preparation of their offspring to respond to olfactory stimuli in a warming environment.
Keywords: Olfactory bulb; Climate change; Forebrain; Neurotransmission; Neurons